Treatment algorithm reduces oxygen use in the Emergency Department. (April 2016) - Sieber, Robert; Osterwalder, Joseph
Abstract : Objectives: Evaluation of an O2 treatment algorithm on the basis of current recommendations to reduce the number of patients unnecessarily treated with O2 in the Emergency Department of a tertiary hospital compared with the traditional application, and analysis of the use of O2 . Design: This was a single-centre cohort study with 4 weeks of observation before and after the introduction of an O2 treatment algorithm. The main outcome measures were the proportion of patients treated with O2, distribution of indications for O2 therapy and occurrence of hypoxia and hypercapnia as undesired effects. Results: The 4-week period before the intervention included 2190 patients and the 4-week period after the intervention included 2122 patients. The indications for O2 therapy were very similar in the two periods. After the intervention, the proportion of patients with supplemental O2 therapy was reduced from 11% (246) to 9% (182) ( P <0.003), a relative decrease of 18%. Undesired effects were similar in nature and frequency in the two observation periods. Conclusion: The introduction of an O2 treatment algorithm in the Emergency Department reduced the number of patients treated with O2, and the nature and frequency of undesired effects was similar before and after the intervention.